Measurement of the Performance of an Economy - Jílková, Eva; Skaličková, Jolana (Management and Administration Journal, 2019)
The success of a national economy and the economic development of a country are mainly assessed based on economic indicators. The Gross Domestic Product (GDP) is the most commonly used indicator at national and regional levels. The informational power of GDP is limited, so alternative ways of measuring economic development and well-being have begun to be used, of which the Human Development Index (HDI) is the best known and the most accessible. The aim of this research is to highlight the areas that are to be considered when assessing economic development and well-being, especially social and environmental factors. One of the objectives is to compare the GDP and the HDI in the V4 countries. There was a gradual, slight increase in HDI without regard to economic cycles and changes in the GDP in the V4 countries between 2007 and 2017.